Effect of an oxygenating agent on oral bacteria in vitro and on dental plaque composition in healthy young adults - Fernandez y Mostajo, Mercedes; van der Reijden, Wil A.; Buijs, Mark J.; Beertsen, Wouter; van der Weijden, Fridus; Crielaard, Wim; Zaura, Egija (Frontiers in Cellular and Infection Microbiology, 2014)
Oral bacteria live in symbiosis with the host. Therefore, when mouthwashes are indicated, selective inhibition of taxa contributing to disease is preferred instead of broad-spectrum antimicrobials. The potential selectivity of an oxygenating mouthwash, Ardox-X® (AX), has not been assessed. The aim of this study was to determine the antimicrobial potential of AX and the effects of a twice-daily oral rinse on dental plaque composition. Material and methods: In vitro, 16 oral bacterial strains were tested using agar diffusion susceptibility, minimum inhibitory and minimum bactericidal concentration tests. A pilot clinical study was performed with 25 healthy volunteers. Clinical assessments and microbiological sampling of supragingival plaque were performed at one month before the experiment (Pre-exp), at the start of the experiment (Baseline) and after the one-week experimental period (Post-exp). During the experiment individuals used AX mouthwash twice daily in absence of other oral hygiene measures. The microbiological composition of plaque was assessed by 16S rRNA gene amplicon sequencing. Results: AX showed high inter-species variation in microbial growth inhibition. The tested Prevotella strains and Fusobacterium nucleatum showed the highest sensitivity, while streptococci and Lactobacillus acidophilus were most resistant to AX. Plaque scores at Pre-exp and Baseline visits did not differ significantly (p = 0.193), nor did the microbial composition of plaque during a period of 7-days non-brushing but twice daily rinsing. Plaque scores increased from 2.21 (0.31) at Baseline to 2.43 (0.39) Post-exp. A significant microbial shift in composition was observed: genus Streptococcus and Veillonella increased while Corynebacterium, Haemophilus, Leptotrichia, Cardiobacterium and Capnocytophaga decreased (p ≤ 0.001). Conclusion: AX has the potential for selective inhibition of oral bacteria. The shift in oral microbiome after one week of rinsing deserves further research.